Bone Mineral Density to Identify Osteopenia and Osteoporosis in Patients of CKD on Maintenance Hemodialysis (Journal of Dhaka Medical College, 2021)
Background : Chronic renal disease changes both quality and quantity of bone through multifactorial influences on bone metabolism, leading to osteopenia, osteoporosis and increased risk of fracture. The objectives of this cross sectional study are to determine the mean bone mineral density (BMD) and to identify osteopenia and osteoporosis in patients of CKD on maintenance hemodialysis.Methods: Twenty three male and 18 female patients with age between 18 and 50 years were enrolled in this study. The BMD of the lumbar vertebral spine (LV) and the neck of femur (FN) were measured in all patients. Data were analyzed using SPSS version 20.0 software and the level of significance was considered as P